2022
DOI: 10.3389/fpls.2022.1015947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arbuscular mycorrhizal fungi on the responses of Ageratina adenophora to Aphis gossypii herbivory

Abstract: The invasive weed Ageratina adenophora can form a positive symbiotic relationship with native arbuscular mycorrhizal fungi (AMF) to promote its invasion ability. However, the function of AMF during the feeding of Aphis gossypii in A. adenophora was poorly understand. This study aimed to investigate the effects of two dominant AMF (Claroideoglomus etunicatum and Septoglomus constrictum) on A. adenophora in response to the feeding of the generalist herbivore A. gossypii. The results showed that A. gossypii infes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
1
5
0
1
Order By: Relevance
“…Du та ін. [21] виявили, що застосування АМ-грибів сприяло підвищенню вмісту азоту, фосфору та калію в рослинах сої, що позначилось на значному збільшені врожайності насіння.…”
Section: аналіз літературиunclassified
“…Du та ін. [21] виявили, що застосування АМ-грибів сприяло підвищенню вмісту азоту, фосфору та калію в рослинах сої, що позначилось на значному збільшені врожайності насіння.…”
Section: аналіз літературиunclassified
“…The spores of S. constrictum were isolated from the rhizosphere soil of A. adenophora in our previous study (Du et al, 2022b). The mycorrhizal inoculum, consisting of fragments of colonized roots, spores, and hyphae of S. constrictum, was propagated using maize as the host plant.…”
Section: Microbial Inoculation Preparationmentioning
confidence: 99%
“…Our previous studies demonstrated that Bacillus cereus has a high abundance in the rhizosphere soil of A. adenophora and R. amethystoides and exerted a positive feedback effect on A. adenophora (Sun et al, 2021;Du et al, 2022a). The AM fungus Septoglomus constrictum was also identified in the rhizosphere soil of A. adenophora and R. amethystoides, which improved the growth of A. adenophora and its resistance to A. gossypii feeding (Yu et al, 2012;Li et al, 2016;Du et al, 2022b). However, the relationship between AMF and Bacillus in the rhizosphere of A. adenophora and R. amethystoides and the effects of this relationship on the competitive growth between the two plants remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In tripartite interactions, AM fungi and aphids can impact each other via their shared host plant, and a wide range of aphid responses have been reported after feeding on mycorrhizal plants. In most cases, aphids benefit by feeding on mycorrhizal plants (Gange et al 1999, 2002, Babikova et al 2014, Gilbert and Johnson 2015, Simon et al 2017, Tomczak and Müller 2017, Maurya et al 2018, Wilkinson et al 2019, Stallmann and Schweiger 2021), but negative (Guerrieri et al 2004, Gehring and Bennett 2009, Babikova et al 2013, Gilbert and Johnson 2015, Garzo et al 2018, Maurya et al 2018, Stallmann and Schweiger 2021, Du et al 2022) or no impacts (Gehring and Bennett 2009, Rizzo et al 2020, Charters et al 2022) on aphids have also been observed. Aphids are pertinent to study because they extract photoassimilates, transmit viruses, and secrete salivary compounds that manipulate plant defense signaling for their own benefit (Edwards and Singh 2006, Hogenhout and Bos 2011, Pitino and Hogenhout 2013, Mondal 2017).…”
Section: Introductionmentioning
confidence: 99%